Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M206 - Koschinsky, Andrea; Schumacher, Mia; Wölfl, Anne-Cathrin (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M206 using a 12kHz Kongsberg EM 122 multibeam echosounder. The expedition took place during 2024-12-01 – 2024-12-30 from Fortaleza (Brazil) to Belem (Portugal) in the Central Atlantic. The major aims of M206 Amazon-GEOTRACES 2 and the related projects is to better constrain the dissolved organic matter (DOM) and trace element (and their isotopes) budgets and net fluxes from the Amazon River system and the large mangrove belt into the Atlantic Ocean. Data were recorded within the EEZs of Brazil and French Guiana as well as outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by Constructor University, provision of the data is supported by the DAM Project Underway Research Data and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder